A study on regulatory compliance of KYC in financial service industry - KUMAR, DR. P. PRAVEEN; MS. R. PUNITHA, (The journal of contemporary issues in business and government, 2020)
The main aim of the study is to determine the need and significance of Know Your Customer (KYC) in the financial sector. A descriptive research design is used in this study since it is most suitable due to the characteristics of the purpose of the study. In this study, a statistical method is used to determine the sample to ensure that the size of the sample is representable for the whole population. The size of the study is 72 and primary data is collected through questionnaire. Tools used in this study are frequency analysis, mean analysis, independent t test and ANOVA. It is found that there is no remarkable differentiation between demographic variables and perception towards the need of KYC.